THE EXISTENCE OF BUYBACK GUARANTEE IN INDONESIAN SECURITY LAW RELATED TO HOUSE PURCHASE FROM DEVELOPER WITH KPR FACILITY: THE EXISTENCE OF BUYBACK GUARANTEE IN INDONESIAN SECURITY LAW RELATED TO HOUSE PURCHASE FROM DEVELOPER WITH KPR FACILITY - Sonya, Assyfa Putri; Suherman, Suherman (PENA LAW: International Journal of Law, 2025)
Buyback Guarantee is generally used in banking practice, but its regulation in Indonesian positive law is still limited. Buyback Guarantee is basically a guarantee given by the developer to the buyer or bank, which ensures the repurchase of the property in the event of inability or failure in the sale and purchase process. In the context of guarantee law, Buyback Guarantee reflects the application of the principle of freedom of contract and the principle of prudence (prudential banking), which aims to provide protection and legal certainty for banks and consumers. However, the Buyback Guarantee agreement is not explicitly regulated in the Civil Code (KUHPerdata), so its existence in Indonesian guarantee law still poses challenges in terms of its application and regulation.